Effects of thermal annealing on the semi-insulating properties of radio frequency magnetron sputtering-produced germanate thin films - dos Santos Filho, S. G.; Sonnenberg, V.; Hora, W. G.; da Silva, D. M.; Kassab, L. R P [UNESP] (Elsevier B.V. Sa, 2012)
We report the effects of thermal annealing on the semi-insulating properties of germanate thin films produced by a radio frequency magnetron sputtering process. Electrical and physical characterizations are presented. In the case of PbO-GeO2 films (annealed and not annealed), the electron diffraction analysis from transmission electron microscopy has shown that the amorphous structure predominates, whereas the annealed PbO-GeO2-AgNO3 (1 wt.%) films presented crystalline nanoparticles in the range of 1 to 9 nm composed of Pb, PbO and Ag4GeO4. Also, not annealed and annealed films were used to produce metal-insulator-semiconductor structures. The electrical properties of these structures were analysed from capacitance-voltage and conductance-voltage characteristics. The results showed that the significant leakage current in the accumulation region in the not annealed films can be increased by the annealing process. In addition, stable semi-insulating layers with an almost constant shifting of the capacitance-voltage characteristics are obtained when annealed PbO-GeO2-AgNO3 (1 wt.%) films are employed. Based on a proposed model accounting for the leakage process, the influence of this leakage on the accumulation capacitance was also established. In addition, the decrease of the dielectric constant in the presence of crystalline nanoparticles was shown. The results obtained indicate that the germanate thin films are potential passivating materials for power device applications. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Germanate; Magnetron sputtering; Metal-insulator-semiconductor structures; Electrical properties